PRESTASI BELAJAR MATEMATIKA DITINJAU DARI SIKAP OPTIMIS DAN PESIMIS SISWA SMA - Lenny Kurniati; Asef Umar Fakhruddin (De Fermat : Jurnal Pendidikan Matematika, 2018)
Pessimism is the attitude or perspective of an individual who is depicted by uncertainty, despair, and there is no hope for something faced. Conversely, optimism is the attitude of someone who sees things positively. This study aims to find out how students who have optimistic and pessimistic attitudes, and find out the differences in students' mathematics achievement between optimistic and pessimistic students, and if there are better ones. This research was conducted in 4 (four) State High Schools in Semarang City, and 498 XII graders has been chosen randomly. The result is that 55% of students are pessimistic, and 45% are optimistic. The research hypothesis that there are differences in mathematics learning achievement between optimistic and pessimistic students has been proven in the results of this study. Significant differences were also confirmed through the results of statistical calculations, and can be indicated by the average score of the optimistic students is higher than pessimistic students. Further discussion is needed on the implications of the results of this study on mathematics education broadly.